Phase Transitions in Foods. - Roos, Yrjo H.; Drusch, Stephan (Academic Press [Imprint] Elsevier Science & Technology Books, 2015)
'Phase Transitions in Foods' assembles the most recent research and theories on the topic, describing the phase and state transitions that affect technological properties of biological materials occurring in food processing and storage. It covers the role of water as a plasticizer, the effect of transitions on mechanical and chemical changes, and the application of modeling in predicting stability rates of change. The volume presents methods for detecting changes in the physical state and various techniques used to analyze phase behavior of biopolymers and food components.